Оптимізація однорідності структури композита на основі cBN - Ткач, С.В. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2007)
The influence of mixing methods onto the homogeneity of composite materials with cBN
grains have been considered. A method of the homogeneity determination for composites has been developed, which uses the data of X-ray microanalysis. It has been established that in dry mixing of powders a conglomeration of the initial components of the same type materials is possible, while the wet mixing of powders with the use of an ultrasonic disperser makes it possible to crush the conglomerates, to improve the homogeneity of the initial mixture and the composite structure.